Systematic review on the reclamation of areas degraded by mining (Research, Society and Development, 2022)
The concern with the economic context and the need for metallic and non-metallic minerals in the current state of world globalization, has caused the abandonment of areas degraded by mineral exploration without any action for their recovery. The objective of this research was to analyze literature about the exploitation of mineral resources for various uses, as well as to seek an answer to the guiding question about the importance of the recovery of these areas after extraction. The method applied was a systematic review with quantitative and qualitative coverage. The data analyzed the occurrence of this type of extraction on a global level. In the Asian continent, China (coal for energy) and Indonesia (sand and gravel for construction) accelerate mineral exploration and this causing environmental impacts such as loss of soil fertility by AMD.  In the African continent (Au extraction) in the open air and in an artisanal way, which determines the presence of mercury in water bodies. On the European continent, Poland, the chemical degradation due to the exploitation of iron and brown coal, is accentuated; on the South American continent, the exploitation of lithium in the Atacama Desert, of gold (in an artisanal way), bauxite, clay, sand, agate, iron, among others, present abandoned areas and without any type or proposal for their recovery, which is causing loss of endemic flora and fauna. Thus, it is affirmed that the economy and the advance of technology are not associated with the importance of maintaining the balance of natural ecosystems and do not evaluate, or do so in an incipient way, the importance of the recovery of areas degraded by mineral exploration.